I beg to differ : navigating difficult conversations with truth and love - Muehlhoff, Tim, 1961- (Downers Grove, IL : INV Books, an imprint of Intervarsity Press, 2014)
How do we communicate with people who disagree with us? In today's polarized world, friends and strangers clash with each other over issues large and small. Coworkers have conflicts in the office. Married couples fight over finances. And online commenters demonize one another's political and religious perspectives. Is there any hope for restoring civil discourse? Communications expert Tim Muehlhoff provides a strategy for having difficult conversations, helping us move from contentious debate to constructive dialogue. By acknowledging and entering into the other person's story, we are more likely to understand where they're coming from and to cultivate common ground. Insights from Scripture and communication theory provide practical ways to manage disagreements and resolve conflicts. We can disagree without being disagreeable. And we can even help another see different points of view and learn from one another. Find out how. - Publisher.
Foreword / Gregg Ten Elshof -- Introduction -- Section one : Understanding communication. Reclaiming the power of words -- What causes verbal dams to rupture? -- Managing and expressing emotions in the midst of disagreement -- Spiritual disciplines : power to resolve conflict -- Section two : Organizing a conversation. Question one : What does this person believe? -- Question two : Why does this person hold this belief? -- Question three : Where do we agree? -- The rules of reciprocation : why steps one through three work -- Question four : Based on all I've learned, how should I proceed? -- Section three : Putting it into practice. Case study one : Disagreeing about finances -- Case study two : Disagreeing over religion in the workplace -- Case study three : Teens and excessive use of video games -- Epilogue.
Includes bibliographical references (pages 207-219).
Keywords: Conflict management -- Religious aspects -- Christianity; Conversation -- Religious aspects -- Christianity; Interpersonal conflict -- Religious aspects -- Christianity